Banking networks and economic growth: From idiosyncratic shocks to aggregate fluctuations - Shohini Kundu; Nishant Vats (European Central Bank (ECB), 2025)
This paper investigates the role of banking networks in the transmission of shocks across borders. Combining banking deregulation in the US with state-level idiosyncratic demand shocks, we show that geographically diversified banks reallocate funds from economies experiencing negative shocks to unaffected regions. Our findings indicate that in the presence of idiosyncratic shocks, financial integration reduces business cycle comovement and synchronizes consumption patterns. Our findings contribute to explaining the Great Moderation and provide empirical support for theories that predict that banking integration facilitates the insurance of region-specific risk and the efficient allocation of resources as markets become more complete.
Keywords: E32; F36; G21; 330; Financial integration; business cycles; economic growth; idiosyncratic shocks; Great Moderation; regional economics